Knowledge, attitudes, and behaviors toward fertility preservation in patients with breast cancer: A cross-sectional survey of physicians - Baek, Soo Yeon; Lee, Kyung-Hun; Kim, Sung-Bae; Gomez, Henry; Vidaurre, Tatiana; Park, Yeon Hee; Ahn, Hee Kyung; Kim, Yoo Seok; Park, In Hae; Ahn, Sung Gwe; Lee, Jeeyeon; Jeong, Jae Ho; et al. (Frontiers in Oncology, 2023)
Background: Fertility is an important issue for young women with breast cancer, but studies about physicians’ knowledge, attitudes, and practices toward fertility preservation (FP) are largely based on Western populations and do not reflect recent international guidelines for FP. In this international study, we aimed to assess the knowledge, attitudes, and practices of physicians from South Korea, other Asian countries, and Latin America toward FP in young women with breast cancer, and identify the related barriers. Methods: The survey was conducted anonymously among physicians from South Korea, other Asian countries, and Latin America involved in breast cancer care between November 2020 and July 2021. Topics included knowledge, attitudes, and perceptions toward FP; practice behaviors; barriers; and participant demographics. We grouped related questions around two main themes—discussion with patients about FP, and consultation and referral to a reproductive endocrinologist. We analyzed the relationships between main questions and other survey items. Results: A total of 151 physicians completed the survey. Most participants’ overall knowledge about FP was good. More than half of the participants answered that they discussed FP with their patients in most cases, but that personnel to facilitate discussions about FP and the provision of educational materials were limited. A major barrier was time constraints in the clinic (52.6%). Discussion, consultations, and referrals were more likely to be performed by surgeons who primarily treated patients with operable breast cancer (FP discussion odds ratio [OR]: 2.90; 95% confidence interval [CI]: 1.24–6.79; FP consultation and referral OR: 2.98; 95% CI: 1.14–7.74). Participants’ knowledge and attitudes about FP were significantly associated with discussion, consultations, and referrals. Conclusion: Physicians from South Korea, other Asian countries, and Latin America are knowledgeable about FP and most perform practice behaviors toward FP well. Physicians’ knowledge and favorable attitudes are significantly related to discussion with patients, as well as consultation with and referral to reproductive endocrinologists. However, there are also barriers, such as limitations to human resources and materials, suggesting a need for a systematic approach to improve FP for young women with breast cancer.